PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN PENDEKATAN KONTEKSTUAL TERHADAP KESADARAN BERAGAMA SISWA SMP NEGERI 3 MARBAU - Tanjung, Abdul Hakim Hanafia Tanjung; Megawati, Betti; Syawaluddin, Fauziahmad (Cahaya Ilmu Bangsa Institute, 2024)
This research aims to determine the effect of Islamic Religious Education Learning with a Contextual Approach on Students' Religious Awareness. This research was conducted at SMP Negeri 3 Marbau with the aim of finding out 1 Islamic Religious Learning with a Contextual Approach at SMP Negeri 3 Marbau. 2) To find out the religious awareness of students at SMP Negeri 3 Marbau. 3) To determine the effect of learning Islamic religious education using a contextual approach in increasing religious awareness of students at SMP Negeri 3 Marbau. This research uses quantitative research methods. The data collection technique used in this research is by using Research Instrument Data Collection. Research Method was carried out using questionnaire data collection techniques and documentation studies. From the data collection carried out in the research, there are still many religious activities carried out at SMP Negeri 3 Marbau because there are still a large number of students who are Muslim, so there is an influence of Islamic religious education learning activities on the moral religious awareness of SMP Negeri 3 Marbau students. This is obtained from the results of calculations using the spss program, namely 1.935 which is greater than the t table at the 5% significance level, namely 1.697 with N = 30. Thus t count > t table obtained from the results is 1.935 > 1.697 with N = 30. Thus , the hypothesis proposed by the author can be accepted that there is an influence of Islamic Religious Education Learning on the Religious Awareness of Students at SMP Negeri 3 Marbau.